Hasil Luaran Janin pada Kehamilan yang Terinfeksi Sifilis yang Diobati dengan Penicillin G: Tinjauan Sistematis: Analisis - Joshua Nathaniel; Tigor Peniel Simanjuntak (Cermin Dunia Kedokteran, 2025)
Background: Syphilis infection during pregnancy can cause congenital syphilis. Syphilis in pregnant women is treated with penicillin to prevent fetal infection and congenital syphilis. A systematic literature review is conducted to determine the efficacy of penicillin G by reviewing outcome parameters. Methods: A systematic literature review following the preferred reporting items for systematic reviews and meta-analysis (PRISMA) guidelines. Results: Through searches on PubMed, Science Direct, and Cochrane using keywords ‘Antibiotics’, ‘Pregnancy’, ‘Syphilis’, and ‘Treatment’, 230 articles were found. Twenty-five articles were duplicates, 135 articles did not meet the inclusion criteria, 75 articles were literature reviews, and 58 articles were not related to pregnant women, resulting in 6 journals that met the inclusion criteria. Conclusion: Penicillin G benzathine is the most common antibiotic used to treat syphilis in pregnancy. A total of 1,190 cases (26.26%) of congenital syphilis were found among 4,531 pregnant women infected with syphilis and receiving penicillin G benzathine therapy. The incidence of congenital syphilis was 2.4% in pregnant women who received therapy since the first trimester. The incidence of congenital syphilis increased 12 times if therapy was given in the second trimester and 33 times if given in the third trimester.